Pengaruh Model Pembelajaran Inquiry Terhadap Efektivitas Belajar Siswa Pada Mata Pelajaran Akidah Akhlak di Mts Daarul Ikhlaash Sangatta Selatan - Fatrah Fatrah; Satriah; Abdul Kadir (Civiliza Publishing, Indonesia., 2026)
This study aimed to determine the influence of the inquiry learning model on students learning effectiveness in the Akidah Akhlak subject at MTs Daarul Ikhlaash Sangatta Selatan and to measure the magnitude of that influence. A quantitative approach with a simple linear regression design was employed. The population consisted of all 34 students of the madrasah, and total sampling was applied. Data were collected through observation, a Likert-scale questionnaire, and documentation. The research instruments were tested for validity and reliability using Microsoft Excel and SPSS 16.0. The results revealed a strong positive correlation (r = 0.8162) between the Inquiry learning model and learning effectiveness. The coefficient of determination (R²) was 66.61%, indicating that the Inquiry model contributed 66.61% to the variation in learning effectiveness, while the remaining 33.39% was influenced by other factors. The regression equation obtained was Y = 10.8058 + 0.6584X. The t-test result (t-count = 7.988 > t-table = 2.038) confirmed that the influence was statistically significant at the 5% level. It was concluded that the Inquiry learning model had a positive and significant effect on students’ learning effectiveness in Akidah Akhlak. The model proved effective in fostering active participation, critical thinking, and better learning outcomes among madrasah students.